A NATIONAL POLICY ON INDONESIA’S INTEGRATED WATER RESOURCE CONSERVATION MANAGEMENT - Chay Asdak; Yulizar; Subiyanto (Indonesian Journal of Forestry Research, 2023)
Changes in global precipitation would affect Indonesia to improve its water resource management system. As most watersheds are in a critical stage nowadays, it is urgent to develop a new plan and policy on water conservation that integrates the most important parameters reasonably. It has the purpose of ensuring that water resources are available for all activities and purposes within the area, especially for future periods. Integrated Water Resources Conservation Management is one of the promising approaches that is being mainly developed, particularly through the participation of all stakeholders. This participation brings equal responsibility to protect and sustainably manage the water resources, which might differ from one area to another in Indonesia. This study shows that it is important to bring up local wisdom practices on water conservation management. These could help overcome the problems related to water management in different locations in Indonesia and encourage all the stakeholders to take responsibility. All the inputs from the stakeholders are very helpful to identify the strategy at the national level, and thus it would minimize the misinterpretation between local and national levels in terms of regulation or policy. Furthermore, the approach strategies provided in this paper could improve the water national policy in Indonesia and minimize the negative potential impacts due to the lack of precipitation in the upcoming years.